问题 解答题
能简便的用简便方法计算.
10
13
÷
35
26
×
7
3
=
5
8
÷(
3
4
+
1
2
)=
1
5
×
4
7
+
3
7
÷5=
④1-
7
9
÷
7
8
=
5
4
-
1
3
÷
5
9
-
2
5
=
⑥(
7
8
+
13
16
)÷
13
16
=
答案

10
13
÷
35
26
×
7
3

=

10
13
×
26
35
×
7
3

=

4
3

5
8
÷(
3
4
+
1
2

=

5
8
÷
5
4

=

5
8
×
4
5

=

1
2

1
5
×
4
7
+
3
7
÷5

=

1
5
×
4
7
+
3
7
×
1
5

=

1
5
×(
4
7
+
3
7

=

1
5
×1

=

1
5

④1-

7
9
÷
7
8

=1-

7
9
×
8
7

=1-

8
9

=

1
9

5
4
-
1
3
÷
5
9
-
2
5

=

5
4
-
1
3
×
9
5
-
2
5

=

5
4
-
3
5
-
2
5

=

5
4
-(
3
5
+
2
5

=

5
4
-1

=

1
4

⑥(

7
8
+
13
16
)÷
13
16

=(

7
8
+
13
16
)×
16
13

=

7
8
×
16
13
+
13
16
×
16
13

=

14
13
+1

=2

1
13

单项选择题
多项选择题